2017
DOI: 10.1007/s10461-017-1973-5
|View full text |Cite|
|
Sign up to set email alerts
|

‘Test and Treat’ Among Women at High Risk for HIV-infection in Kampala, Uganda: Antiretroviral Therapy Initiation and Associated Factors

Abstract: Data on implementation of ‘Test and Treat’ among key populations in sub-Saharan Africa are still limited. We examined factors associated with prompt antiretroviral therapy/ART (within 1 month of HIV-positive diagnosis or 1 week if pregnant) among 343 women at high risk for HIV infection in Kampala-Uganda, of whom 28% initiated prompt ART. Most (95%) reported paid sex within 3 months prior to enrolment. Multivariable logistic regression was used to determine baseline characteristics associated with prompt ART. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…Our analysis identified some groups (for example, younger men and mobile populations) as often being slower to start ART, probably because the health service delivery mechanisms are not appropriate to their needs. These observations are in keeping with the findings from other studies [ 12 , 16 , 22 , 28 , 58 ]. As has been demonstrated recently with the findings for the ANRS 12249 TasP Cluster-Randomised Trial, even in the controlled environment of a trial, ensuring prompt treatment may be challenging [ 15 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our analysis identified some groups (for example, younger men and mobile populations) as often being slower to start ART, probably because the health service delivery mechanisms are not appropriate to their needs. These observations are in keeping with the findings from other studies [ 12 , 16 , 22 , 28 , 58 ]. As has been demonstrated recently with the findings for the ANRS 12249 TasP Cluster-Randomised Trial, even in the controlled environment of a trial, ensuring prompt treatment may be challenging [ 15 ].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we found a high uptake of HIV test and treat program where 92.4% of all individuals who were tested HIV positive accepted ART initiation within one month of HIV diagnosis. This therefore demonstrates a significant progress in the uptake of test and treat program in Uganda particularly and Africa at large, from 28% among women at risk of HIV infection in Kampala [7], 49.1%among children in Uganda [6], and 65% in Zimbabwe [8]. This high uptake of test and treat could have resulted from increased sensitization of the community on the benefits of early ART initiation for clients who are HIV positive, and if sustained will lead to attainment of the UNAIDS2030 target of 95-95-95.…”
Section: Discussionmentioning
confidence: 79%
“…Socio-demographic characteristics such as younger age and being widowed/separated were earlier identified in Uganda [7] as being associated with low chances of prompt ART initiation. This was however not the case in our study as both age and marital status did not have any significant association with failure to enroll clients under the test and treat policy.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations